Efectos del fenómeno "El Niño 1997-98" en el fitoplancton de la bahía de Catarindo, Mollendo - Vizcarra, Amparo (1999)
The present work 01 "El Niño" effect on annual cycle 01 phytoplankton was carried out among January of 1997 and September 01 1998. The samples were obtained two times by month with a Niskin bottle to 0,5 m depth in a station located at 17°00'56"lS and 72°02'15" LW. The Uthermol's method modified was followed for the analysis. The major phytoplanktonic density was recorded in summer of 1997 with values range between 3335 and 21 705 cel x 50 mL associated to predominance of the silicollagellate Dyctiocha fibula, which in February represented 76% 01 total density. A great decrease 01 phytoplankton density was recorded since June of 1997 until January 01 1998 (50 to 688 cel x 50mL) characterizing oligotrophic conditions associated to positive deviations of temperature that reached in January-98 4,9°C upon normality. This produced an interruption of the spring upwelling and altering the phytoplankton annual cycle. The phytoplankton density range between 1114 Y 10978 cel x 50 mL since February to September 1998. It was associated to positive deviations 01 temperature, which decrease until O,2°C in August. September showed negative anomaly of 0,8 °C. These was followed for a recovering of the normal environmental conditions, and are related with the beginning of phytoplanktonic density increase, which would manifested in spring of 1998. In general, the diatoms predominated throughout the period 01 study constituting 62%, of total density. Protoperidinium obtusum indicator of cold water recently recorded in March 1997.